Residential buildings renewal towards to the Smart concept - Golej, Julius (EAI Endorsed Transactions on Smart Cities, 2017)
The current global trends lead to fulfilment of specified environmental and economic objectives in all sectors of national economies. Buildings form a basic pillar of smart cities concept where all life processes and nerve centres of social life are read, in order to radically improve quality of life, opportunity, prosperity, social and economic development, thanks to the use of the new technology. The building sector has been identified by various studies as a sector that offers considerable potential for the cost-effective reduction of greenhouse gas emissions, making it an important field for climate protection action. A significant role towards realizing these objectives has in particular the implementation of the latest technologies and technical procedures in all processes at all levels. Smart buildings are no longer considered individually, but as a part of complex ecosystem. They must be adapted to the expectations of future users if they are to be properly used. This paper deals with the problematics of current technological, environmental and economic trends in renewal of residential buildings.